Isokinetic evaluation of anterior cruciate ligament reconstruction: quadriceps tendon versus patellar tendon - Pigozzi, F.; Di Salvo, V.; Parisi, A.; Giombini, A.; Fagnani, F.; Magini, W.; Franceschi, F.; Denaro, E. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: The goal of this prospective randomized study was to compare the isokinetic recovery of thigh strength after anterior cruciate ligament (ACL) reconstruction by using patellar or quadriceps tendon as graft at the 6th month follow-up. METHODS: The authors evaluated 48 patients who underwent arthroscopic ACL reconstruction using patellar tendon (PT group) or quadriceps tendon (QT group) as autograft after a 6 months follow-up undergoing the following tests: the Ergojump Bosco System springboard and Universal's FITNET computerized isokinetic system. RESULTS: The counter movement jump (CMJ) test showed a 24 % (p<0.01) strength deficit in patients operated with patellar tendon and 11 % in the quadriceps tendon group. Also in the leg press test the greater differences in strength (p<0.05) were verified in the patellar tendon group, above all the peak torque (PT) test carried out at 3 repetitions (15 %). CONCLUSIONS: The strength deficit found in the subjects operated with quadriceps tendon were statistically lower in comparison to that verified in the patellar tendon group. A good recovery in thigh strength after 6 months in patients operated with quadriceps tendon could encourage the use of this kind of graft in order to achieve an easier rehabilitation and a faster release of the patient to daily and sports activity.